Don't Look Now: British Cinema in The 1970s - Newland, Paul (Intellect, Limited, 2010)
While postwar British cinema and the British new wave have received much scholarly attention, the misunderstood period of the 1970s has been comparatively ignored. Don't Look Now uncovers forgotten but richly rewarding ?lms, including Nicolas Roeg's Don't Look Now and the ?lms of Lindsay Anderson and Barney Platts-Mills. This volume offers insight into the careers of important ?lm-makers and sheds light on the genres of experimental ?lm, horror, and rock and punk ?lms, as well as representations of the black community, shifts in gender politics, and adaptations of television comedies. The contributors ask searching questions about the nature of British ?lm culture and its relationship to popular culture, television, and the cultural underground.
https://katalog.adlr.link/Record/76-EBC540065